2017
DOI: 10.18805/lr.v0i0.7649
|View full text |Cite
|
Sign up to set email alerts
|

Influence of seed coat compactness around cotyledons, protein andmineral composition on mechanical strength of soybean[Glycine max (L.) Merrill] seed coat

Abstract: The critical problem of soybean seed is susceptibility to mechanical processes due to structural limitations of seed and seed coat. The X-radiography of soybean seed revealed the orientation of seed coat around the cotyledons and cultivars like JS 335, JS 9752, JS 71-05, JS 95-60, MACS 124, Pusa 40, Punjab 1 and Type 49 had very compact seed coat around cotyledons. In NRC 12, NRC 37, RKS 18 and SL 525 where the gap between seed coat and cotyledons was significantly very high and non uniform making seed coat ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 9 publications
(10 reference statements)
1
5
0
Order By: Relevance
“…These results indicate that the impermeable black seed coat of Bhatt contains comparatively more protein than the permeable white seed coat of JS 335. Similar differences were found by Kuchlan et al (2018) and Mullin & Xu (2001) in seed coats of soybean Seed coats of Bhatt contained more phenols (6.76 AE 0.47 mgÁg À1 ) than those of JS 335 (0.71 AE 0.53 mgÁg À1 ). The relationship between phenol content and permeability is well established (Marbach & Mayer 1974).…”
Section: Seed Coat Proteins Phenols and Tanninssupporting
confidence: 74%
See 1 more Smart Citation
“…These results indicate that the impermeable black seed coat of Bhatt contains comparatively more protein than the permeable white seed coat of JS 335. Similar differences were found by Kuchlan et al (2018) and Mullin & Xu (2001) in seed coats of soybean Seed coats of Bhatt contained more phenols (6.76 AE 0.47 mgÁg À1 ) than those of JS 335 (0.71 AE 0.53 mgÁg À1 ). The relationship between phenol content and permeability is well established (Marbach & Mayer 1974).…”
Section: Seed Coat Proteins Phenols and Tanninssupporting
confidence: 74%
“…Similar differences were found by Kuchlan et al . (2018) and Mullin & Xu (2001) in seed coats of soybean genotypes. However, further studies are needed to establish the impact of protein content on seed coat permeability.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that HCT silencing through RNAi and knockout results in lower lignin content and reduces growth in the plant Arabidopsis [ 64 , 65 , 66 , 67 , 68 ]. Higher levels of lignin in the seed are associated with higher physiological quality, reduced damage from moisture, less damage caused by storage fungi, and less mechanical damage [ 19 , 69 , 70 ]. Additionally, soybean varieties with black seed coats have better storability due to having smaller pores in their membranes and higher lignin contents [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding seed quality, it has already been observed that genotypes with high levels of lignin in their seed coats present greater thickness and, consequently, greater tissue resistance to possible physical damage due to moisture, mechanical damage, and/or the presence of pathogens [ 14 , 15 , 16 , 17 , 18 , 19 ]. Lignin is also associated with more thickness in other tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Hilum is another prime seed part that delivers nutrients and photosynthates to the developing embryo and when damaged leads to seed infections and inferior seed quality. Likewise, properties of seed coat surface like cutin deposition, cuticle cracks, gap between seed coat and cotyledon and depositions influence water permeability, fungal invasion, and ultimately seed longevity in soybean (Ranathunge et al, 2010;Kuchlan et al, 2018).…”
Section: Intrinsic Factorsmentioning
confidence: 99%